Identification of GATA6 sequence variants in patients with congenital heart defects - Maitra, Meenakshi (2010)
While the etiology for the majority of congenital heart disease (CHD) remains poorly understood, the known genetic causes are often the result of mutations in cardiac developmental genes. GATA6 encodes for a cardiac transcription factor, which is broadly expressed in the developing heart and is critical for normal cardiac morphogenesis, making it a candidate gene for congenital heart defects in humans. The objective of this study was to determine the frequency of GATA6 sequence variants in a population of individuals with a spectrum of cardiac malformations. The coding regions of GATA6 were sequenced in 310 individuals with CHD. We identified two novel sequence variations in GATA6 that altered highly conserved amino acid residues (A178V and L198V) and were not found in a control population. These variants were identified in two individuals (one with tetralogy of Fallot and the other with an atrioventricular septal defect in the setting of complex CHD). Biochemical studies demonstrate that the GATA6 A178V mutant protein results in increased transactivation ability when compared to wildtype GATA6. These data suggest that non-synonymous GATA6 sequence variants are infrequently found in individuals with CHD.